Digital Parenting in the Era of Artificial Intelligence: The Role of Parents in Guiding Early Childhood Interaction with Smart Technology - Mukhtar, Zulfadhly; Selvi, Issaura Dwi; Mukhtar AH, Nurkamelia; Abrillia Jasandra (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2025)
This study aims to explore the role of parents in guiding early childhood interactions with artificial intelligence (AI)-based technology within the framework of digital parenting. Using a descriptive qualitative approach, data were collected through in-depth interviews, participant observation, and documentation involving ten parents of children aged 4–6. The findings indicate that active mediation was the most commonly applied strategy (8 out of 10 parents), though restrictive mediation remains dominant in limiting access and screen time. Co-using was the least practiced due to time constraints and low digital literacy. A key finding highlights parents' limited understanding of AI principles, which hinders reflective and educational engagement during children’s AI use. This study introduces a novel contribution by integrating parental AI literacy into the parental mediation model and proposes a theoretical modification of digital parenting. Practical implications include the need for parental AI literacy modules and child technology design that fosters active family involvement. These findings underscore the shift in digital parenting from mere technical control toward reflective guidance grounded in AI literacy. Keywords: artificial intelligence, digital parenting, early childhood